2015
DOI: 10.3354/dao02895
|View full text |Cite
|
Sign up to set email alerts
|

Mucocutaneous lesions in free-ranging Atlantic bottlenose dolphins Tursiops truncatus from the southeastern USA

Abstract: Mucocutaneous lesions were biopsied from free-ranging Atlantic bottlenose dolphins Tursiops truncatus inhabiting the Indian River Lagoon (IRL), Florida, and estuarine waters of Charleston (CHS), South Carolina, USA, between 2003 and 2013. A total of 78 incisional biopsies from 58 dolphins (n = 43 IRL, n = 15 CHS) were examined. Thirteen dolphins had 2 lesions biopsied at the same examination, and 6 dolphins were re-examined and re-biopsied at time intervals varying from 1 to 8 yr. Biopsy sites included the ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Higher mercury levels have been documented among IRL dolphins compared to CHS dolphins [16, 17]. Both IRL and CHS dolphin populations have been reported to have orogenital neoplasia that impact immune function and that are associated with novel papillomavirus and herpesvirus infections [1822]. Additionally, IRL dolphins have reported subclinical or clinical infections of cetacean morbillivirus, lacaziosis and chlamydiosis that result in various, often severe, immunologic perturbations [2325].…”
Section: Methodsmentioning
confidence: 99%
“…Higher mercury levels have been documented among IRL dolphins compared to CHS dolphins [16, 17]. Both IRL and CHS dolphin populations have been reported to have orogenital neoplasia that impact immune function and that are associated with novel papillomavirus and herpesvirus infections [1822]. Additionally, IRL dolphins have reported subclinical or clinical infections of cetacean morbillivirus, lacaziosis and chlamydiosis that result in various, often severe, immunologic perturbations [2325].…”
Section: Methodsmentioning
confidence: 99%
“…In a related study, we recently described mucocutaneous lesions identified in biopsies of HERA dolphins taken between 2003 and 2013 (Bossart et al 2015). Pathologic diagnoses were OP (40%), PC (17%), tattoo skin disease (TSD) (15%), nonspecific chronic to chronic-active dermatitis (15%), and epidermal hyperplasia (13%).…”
Section: Orogenital Papillomatosismentioning
confidence: 99%
“…This was the first longterm study documenting the various types, combined prevalence, and progression of mucocutaneous lesions in dolphins from the southeastern USA. Environmental and anthropogenic factors were considered to play a role in the pathogenesis, diversity, and prevalence of many of these mucocutaneous lesions (Bossart et al 2015).…”
Section: Orogenital Papillomatosismentioning
confidence: 99%
“…Two delphinid gammaherpesviruses (DeHV-4 and −5) have also been found with PV co-infections [36,37]. Orogenital sessile papillomas (OP) associated with novel PV and herpesvirus (HV) infections were first noted in wild bottlenose dolphins from southeast Atlantic coastal waters in 2005 as part of a capture/release health assessment study from 2003 to 2015 [6,[38][39][40]. Lingual and genital mucosal lesions were all grossly and microscopically similar sessile papillomas [40].…”
Section: Papillomavirusesmentioning
confidence: 99%
“…Orogenital sessile papillomas (OP) associated with novel PV and herpesvirus (HV) infections were first noted in wild bottlenose dolphins from southeast Atlantic coastal waters in 2005 as part of a capture/release health assessment study from 2003 to 2015 [6,[38][39][40]. Lingual and genital mucosal lesions were all grossly and microscopically similar sessile papillomas [40]. A novel PV was isolated from a genital papilloma which was designated as TtPV-2 [16].…”
Section: Papillomavirusesmentioning
confidence: 99%